2019
DOI: 10.3384/ijal.1652-8670.18421
|View full text |Cite
|
Sign up to set email alerts
|

Care facilities for Germans in Thailand and Poland: making old age care abroad legitimate

Abstract: This article looks at old age care facilities abroad that target people who live in Germany. Such facilities have been established in Southeast Asia (mainly Thailand) and in Eastern Europe (mainly Poland). Given that they challenge central guiding orientations for old age care in Germany, considerable criticisms are levelled at them, and their use is viewed with distinct scepticism. Nevertheless, some of these facilities succeed in sustaining considerable demand from Germany over quite a few years. In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Opportunities to increase autonomy and lifestyle through geographical mobility has a longer history, but its manifestation in contemporary retirement migration to Latin America should be understood against the changing backdrop of state responsibility for provision of elder-care, as well as the shift in the household from producer to consumer of care (Hochschild, 2013). As Bender et al (2018) point out, provision of care is an important amenity for some older migrants, spawning a growing industry in lower-income countries ( see also Bender and Schweppe, 2019).…”
Section: Ageing In Mobilitymentioning
confidence: 99%
“…Opportunities to increase autonomy and lifestyle through geographical mobility has a longer history, but its manifestation in contemporary retirement migration to Latin America should be understood against the changing backdrop of state responsibility for provision of elder-care, as well as the shift in the household from producer to consumer of care (Hochschild, 2013). As Bender et al (2018) point out, provision of care is an important amenity for some older migrants, spawning a growing industry in lower-income countries ( see also Bender and Schweppe, 2019).…”
Section: Ageing In Mobilitymentioning
confidence: 99%
“…Still, there exists evidence, even if a lot of it is testimonial (Schwiter, Brütsch, and Pratt 2020;Bally-Zenger, Eckenwiler, and Wild 2017), that the care that they are providing is often not only not worse than the one available in care homes within higherincome countries but better thanks to their superior staff-to-resident ratios. For example, the Polish town of Zabelków has a care home with seventy-five German residents which, according its German manager, can pride itself on a staff-to-resident ratio of one to five or one to six (by comparison, the ratio for people with moderate care needs in Germany is one to thirteen according to estimates by Alzheimer Europe (2020)), as well as on a workforce that is alleged to be as highly trained as staff in German care homes (Großmann and Schweppe 2020;Bender and Schweppe 2019). In a video report by the Rheinische Post, several German residents and their family members express high levels of contentment about how the Polish care home is run.…”
Section: Well-beingmentioning
confidence: 99%
“…Fourth, any linguistic differences and cultural differences that end up being manifested within foreign care homes might not be (fully) noticed by, or simply be inconsequential for, care home residents with severe cognitive impairments as a result of these impairments (cf. Schwiter, Brütsch, and Pratt 2020;Bender and Schweppe 2019). In particular, it has been suggested that linguistic differences matter little when people with dementia have (largely) lost the ability for verbal communication (cf.…”
Section: Well-beingmentioning
confidence: 99%
See 2 more Smart Citations